2012
DOI: 10.1111/j.1474-9726.2012.00858.x
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+ dysregulation in neurons from transgenic mice expressing mutant presenilin 2

Abstract: SummaryMutations in amyloid precursor protein (APP), and presenilin-1 and presenilin-2 (PS1 and PS2) have causally been implicated in Familial Alzheimer's Disease (FAD), but the mechanistic link between the mutations and the early onset of neurodegeneration is still debated. Although no consensus has yet been reached, most data suggest that both FAD-linked PS mutants and endoge-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
134
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 86 publications
(147 citation statements)
references
References 39 publications
11
134
1
1
Order By: Relevance
“…Moreover, ER-mitochondrial contacts are increased and ER-mitochondrial crosstalk is enhanced in PSEN1 knockout cells, in cells overexpressing the FAD mutant PSEN2, and in fibroblasts from FAD and sporadic AD patients (Zampese et al 2011;Area-Gomez et al 2012;Kipanyula et al 2012). Thus, PSENs are critically positioned where ER and mitochondria communicate and share contents (e.g., calcium, lipids, ATP).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, ER-mitochondrial contacts are increased and ER-mitochondrial crosstalk is enhanced in PSEN1 knockout cells, in cells overexpressing the FAD mutant PSEN2, and in fibroblasts from FAD and sporadic AD patients (Zampese et al 2011;Area-Gomez et al 2012;Kipanyula et al 2012). Thus, PSENs are critically positioned where ER and mitochondria communicate and share contents (e.g., calcium, lipids, ATP).…”
Section: Discussionmentioning
confidence: 99%
“…S1, respectively). and was very recently used by two groups to monitor free Ca 2+ levels in the ER lumen of mammalian cells (Ravier et al, 2011;Kipanyula et al, 2012). To efficiently target the D4 probe to the lumen of plant cell ER, we followed the same cloning strategy adopted for the production of the CRT-D1ER construct.…”
Section: In Plants Rises In Cytosolic Camentioning
confidence: 99%
“…To efficiently target the D4 probe to the lumen of plant cell ER, we followed the same cloning strategy adopted for the production of the CRT-D1ER construct. The Arabidopsis CALRETICULIN1A (Christensen et al, 2010) signal peptide was fused upstream of the D4ER Cameleon reporter (Kipanyula et al, 2012), and the entire coding sequence was placed under the control of a single cauliflower mosaic virus (CaMV) 35S promoter. The resulting construct, CRT-D4ER (Fig.…”
Section: In Plants Rises In Cytosolic Camentioning
confidence: 99%
“…16,52,53 This could be a general mechanism in many neuropathological processes, since disturbances in the formation of peri-mitochondrial Ca 2+ microdomains has been already reported to contribute to other disorders, such as for example Alzheimer disease. 25 In parallel, strong evidence underlines the importance of transcriptional dysregulation in HD and of the ability of mutated Figure 2 (See opposite page). List of the 67 Ca 2+ -related genes in cluster 22 that are downregulated in the model systems of HD shown on the top.…”
Section: Discussionmentioning
confidence: 97%
“…As to the ER, mutated Htt (but not the wild type protein) has been claimed to interact directly with the C-terminal portion of the inositol 1,4,5-trisphosphate (InsP 3 ) receptor type 1 (InsP 3 R1), 16 sensitizing it to InsP 3 24 and thus modulating the efflux of Ca 2+ from the ER. As suggested for other neurological disorders, 25 this could in turn affect the ability of mitochondria to take up Ca 2+ , that is known to depend on the close proximity of mitochondria to the Ca 2+ releasing ER. A recent finding has shown that InsP 3 R silencing reduces the aggregation of mutated Htt, 26 underlining the importance of the interaction between the two proteins for the molecular pathogenesis of HD.…”
Section: +mentioning
confidence: 90%